2007
DOI: 10.1590/s0102-86502007000200008
|View full text |Cite
|
Sign up to set email alerts
|

Do lesions of the enteric nervous system occur following intestinal ischemia/reperfusion?

Abstract: Purpose:To evaluate tissue lesions, especially those of the intestinal innervation, in an excluded jejunal loop subjected to ischemia and reperfusion in rats. Methods: To evaluate the role of ischemia and reperfusion lesions in an excluded intestinal loop, four groups of 20 rats were set up: control group (GCEI7) and three experimental groups (GIREI7, GIREI14 and GIREI28). They were all subjected to exclusion of an intestinal segment of six centimeters in length, at a distance of 10 centimeters from the Treitz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…47,48 Ganglion cell numbers decrease as early as 7 days after I/R. 49 Irregularity, pyknocytosis, and degenerative changes in nuclear morphology have also been noted. 50 Although many of these alterations are observed in a delayed fashion, a recent study found that pyknocytosis and vacuolization such as cell swelling could be observed as early as 2 h after reperfusion following 10 min of intestinal ischemia in a rodent model.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Ganglion cell numbers decrease as early as 7 days after I/R. 49 Irregularity, pyknocytosis, and degenerative changes in nuclear morphology have also been noted. 50 Although many of these alterations are observed in a delayed fashion, a recent study found that pyknocytosis and vacuolization such as cell swelling could be observed as early as 2 h after reperfusion following 10 min of intestinal ischemia in a rodent model.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate release during I/R could also cause toxicity in the enteric nervous system, which could cause motility alterations [32] . One recent study found that intestinal I/R causes myenteric plexus ganglion cell reduction and death [33] . This suggests that the NMDA receptor could be related to the functional alterations induced in the intestine by I/R.…”
Section: Issnmentioning
confidence: 99%
“…However, some studies insist that low ligation can preserve autonomous innervation along the proximal colonic limb and consequently preserve colonic function including motility [ 11 ]. Additionally, it was reported that colonic ischemia and reperfusion could decrease the number of ganglionic cells in the myenteric plexus, which did not recover in the late postoperative period in an animal model [ 24 ]. This result may explain newly developed constipation after anterior resection without mechanical abnormalities in imaging studies.…”
Section: Discussionmentioning
confidence: 99%